Global Research Trends on the Integration of Local Wisdom and Students' Religiosity in Science Education: A Bibliometric Analysis of Scopus Publications (2020–2025) - Sutrini Sutrini; Ahsanul In'am; Romelah Romelah (Yayasan Darussalam Bengkulu, 2026)
Character education in the era of digital disruption faces serious challenges due to the decline of students’ moral and spiritual values influenced by digital media exposure and global social transformation. Character education in the era of digital disruption faces serious challenges in the form of the weakening of students’ moral and spiritual values due to the influence of digital media and global social changes. Although many studies have highlighted the importance of local wisdom in character education, most still focus on moral and ethical aspects, rather than specifically on strengthening students’ religious values. There are not yet many conceptual models that systematically and measurably integrate local cultural practices with religious education. This study employed a quantitative approach using bibliometric research methods. The data were obtained from the Scopus database through a process of searching, screening, and selecting articles based on keywords related to students’ religiosity and local wisdom. A total of 159 English-language journal articles were analyzed using Bibliometrix and Biblioshiny software. Data analysis was conducted through annual scientific production, co-authorship analysis, country collaboration, co-citation analysis, and thematic mapping to identify research trends and scientific collaboration networks. The findings indicate that publication trends increased significantly after 2022 and reached their peak in 2025. Indonesia emerged as the leading contributor in terms of publications and international research collaboration. Themes such as local wisdom, students, culture, and sustainability became dominant research topics that developed toward interdisciplinary approaches in character education and sustainable development. This study concludes that students’ religiosity based on local wisdom holds a strategic position in strengthening character education in the global era. The study contributes by providing a comprehensive scientific mapping that can serve as a foundation for future research development and educational policies based on values, culture, and sustainability.